The Effects of Exergames on the Attitudes of Secondary School Female Students towards Physical Education - Yakup Zühtü Birinci; Nimet Haşıl Korkmaz; Murat Deniz; Serkan Pancar; Gökhan Çetinoğlu; Hüseyin Topçu (Journal of Educational Issues, 2024)
Growing studies show that exergames (EG) which can combine physical activity (PA) and games is an effective educational tool in physical education (PE). The purpose of this research was to evaluate the effect of dance-based EG on the attitude of 8th grade female students towards PE. The research group consists of 15 female students who are educated in the 8th grade of secondary education in the public school of Bursa province. Participants performed dance-based EG for 80 minutes (3 sets of 20 minutes sessions, 10 minutes rest between sessions), 3 days a week for 8 weeks. Music and dance content were changed after each 20-minute game. Participants answered the Physical Education and Sports Attitude Scale (PESAS) before the first exergame session and at the end of 8 weeks. Shapiro-Wilk and Kolmogorov-Smirnov tests were used to determine whether the variables are normally distributed. Mann-Whitney U test was used for pairwise comparisons, Kruskal-Wallis Analysis of Variance was used for multiple comparisons. The relationships between the variables were examined with the Spearman-correlation coefficient. A statistically significant difference was found between the participants’ PESAS pre-test and post-test scores (p = 0.001). Based on the results of the study it can be concluded that dance-based EG is useful for developing positive attitudes towards PE among female students.